Sejarah Kedudukan Taqnīn dan Posisi Taqnīn dalam Hukum Islam: History of Taqnīn's Position and the Position of Taqnīn in Islamic Law - Diyarti, Sisi; Salma, Salma; Meirison, Meirison (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Qanun is a series of choices that guide human life in acting and must be obeyed even though they feel pressure from experts. Currently, the challenged Qanun is considered a formalization of Islamic regulations, especially sharia regulations, which are considered restrictive and generally relevant by public authorities. The presence of Qanun in recent times is a consequence of the many regulations that have developed, especially due to the influence of European regulations in general. This research uses qualitative research methods with library research techniques. This research aims to analyze the history of taqnīn, procedures for forming qanuns, the coercive power of qanuns, and the position of qanuns in Islamic law. The research results show that currently qanun are seen as part of Islamic guidelines, especially sharia guidelines prepared by open experts that are both restrictive and generally relevant. The presentation of Qanun in this modern era, from one point of view, is seen as the progress of Islam in developing its Shari'a and implementing the guidelines contained therein. According to a limited view, the use of the term qanun in Islam can mean unclear guidelines or guidelines created by humans, where the resulting guidelines are the result of the ijtihad of a person or group of scientists on a problem. According to the general view, Qanun is a series of choices that guide human life in acting and must be obeyed regardless of pressure from public officials.